Effects of Very Low Nicotine Content Cigarettes on Smoking Behavior and Biomarkers of Exposure in Menthol and Non-menthol Smokers. (23rd December 2019) - Denlinger-Apte, Rachel L; Kotlyar, Michael; Koopmeiners, Joseph S; Tidey, Jennifer W; Luo, Xianghua; Benowitz, Neal L; Jensen, Joni A; Ikuemonisan, Joshua O; Pacek, Lauren R; Smith, Tracy T; Vandrey, Ryan; Donny, Eric C; et al.
Abstract: Introduction: Because 30% of cigarettes sold in the United States are characterized as menthol cigarettes, it is important to understand how menthol preference may affect the impact of a nicotine reduction policy. Methods: In a recent trial, non-treatment-seeking smokers were randomly assigned to receive very low nicotine cigarettes (VLNC; 0.4 mg nicotine/g tobacco) or normal nicotine cigarettes (NNC; 15.5 mg/g) for 20 weeks. On the basis of preference, participants received menthol or non-menthol cigarettes. We conducted multivariable regression analyses to examine whether menthol preference moderated the effects of nicotine content on cigarettes per day (CPD), breath carbon monoxide (CO), urinary total nicotine equivalents (TNE), urinary 2-cyanoethylmercapturic acid (CEMA), and abstinence. Results: At baseline, menthol smokers ( n = 346) reported smoking fewer CPD (14.9 vs. 19.2) and had lower TNE (52.8 vs. 71.6 nmol/mg) and CO (17.7 vs. 20.5 ppm) levels than non-menthol smokers ( n = 406; p s < .05). At week 20, significant interactions indicated that menthol smokers had smaller treatment effects than non-menthol smokers for CPD (–6.4 vs. –9.3), TNE (ratio of geometric means, 0.22 vs. 0.10) and CEMA (ratio, 0.56 vs. 0.37; p s < .05), and trended toward a smaller treatment effect for CO (–4.5 vs. –7.3 ppm; p = .06). Odds ratios for abstinence at week 20 were 1.88 (95% confidence interval [CI] = 0.8 to 4.4) for menthol and 9.11 (95% CI = 3.3 to 25.2) for non-menthol VLNC smokers ( p = .02) relative to the NNC condition. Conclusions: Although menthol smokers experienced reductions in smoking, toxicant exposure, and increases in quitting when using VLNC cigarettes, the magnitude of change was smaller than that observed for non-menthol smokers. Implications: Results of this analysis suggest that smokers of menthol cigarettes may respond to a nicotine reduction policy with smaller reductions in smoking rates and toxicant exposure than would smokers of non-menthol cigarettes.